Diffuse large B-Cell lymphoma in a patient with necrotizing fasciitis secondary to silicone biopolymer implants in buttock (2017)
We describe the case of a 58-year-old woman who underwent buttock silicone biopolymer implant surgery. Five years following the surgery she consulted for gluteal region and thigh swelling, warm sensation, and pain. Physical examination revealed gluteal dermatosis also affecting the thighs bilaterally, exhibiting ulcers and skin necrosis. The patient received several surgical procedures including extraction of the permanent fillers and flap and skin graft reconstructions (Figure 1A). Ten months later, the patient consulted once again for a left thigh 14 × 11 × 4 cm mass associated with inguinal lymphadenopathy (Figure 1B).